Analisis Faktor-Faktor yang Mempengaruhi Minat Berwirausaha di Kalangan Mahasiswa (Studi Kasus: Institut Teknologi Del) - Pasaribu, Romantri; Simanjuntak, Mariana (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study aims to analyze the factors influencing entrepreneurial interest among students at Del Institute of Technology. The research focuses on three main factors: entrepreneurial motivation, student creativity, and entrepreneurship learning models. Using a quantitative approach with a survey method, this study involved 36 respondents from 2nd, 3rd, and 4th-year students selected through simple random sampling. The analysis results show that student creativity and entrepreneurial interest have very high index values, while entrepreneurial motivation demonstrates a high value, and the entrepreneurship learning model is at a moderate level. Validity tests prove all questions in the questionnaire are valid, while reliability tests indicate that the variables of entrepreneurial motivation, entrepreneurship learning model, and entrepreneurial interest are reliable. However, the student creativity variable did not show adequate reliability. These findings provide important insights for developing effective strategies in promoting entrepreneurship among students, although further research is needed to investigate the factor of student creativity more deeply.